A review of the genus Micropachyiulus Verhoeff, 1899 and description of the related Armeniopachyiulus gen. nov. (Diplopoda: Julida: Julidae: Pachyiulini) - Vagalinski, Boyan; Evsyukov, Aleksandr P.; Chumachenko, Yuri A.; Zabiyaka, Igor Y. (Zootaxa, 2023)
The European millipede genus Micropachyiulus Verhoeff, 1899 is revised based on type and non-type material, and on the available literature. The genus Hylopachyiulus Attems, 1904 is established as a junior subjective synonym of Micropachyiulus, syn. nov. Micropachyiulus ocellatus (Antić & Akkari, 2018) is thus listed as a new combination, comb. nov. Two new species—Micropachyiulus caucasicus sp. nov. and M. filiformis sp. nov.—are described from Russia and Romania, respectively. In addition, a presumably closely related monospecific genus, Armeniopachyiulus gen. nov., and its sole species A. pokr gen. et sp. nov. are described from Armenia. A brief discussion on the systematics and distribution of the studied taxa is presented.